Artikel PENGEMBANGAN LEMBAR KERJA MAHASISWA BERBASIS DIRECT INSTRUCTION PADA MATERI BESARAN DAN PENGUKURAN - Ihsan Avif Pratama; Sukarno Sukarno; Fibrika Rahmat Basuki (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2023)
This study aims to determine the characteristics of student worksheets based on direct instruction on the material of magnitude and measurement. The study is a research and development (using the 4D model. This research phase includes Define, Design, and Development. The subjects of this study were one material expert, one media expert, one linguist and students who had studied the experimental physics course consisting of 10 students. The data collection instruments used were expert validation sheets and student questionnaires. Data validation results and student responses were analyzed descriptively. This study produced student worksheets based on direct instruction on quantities and measurements. This worksheet contains five experiments, namely length measuring instruments, mass measuring instruments, temperature measuring instruments, time measuring instruments, and current and voltage measuring instruments. The results of the material expert validation were 78% in the good category, the media expert validation results were 92% in the very good category, the linguist validation results were 91% in the very good category, and the test results of student respondents on the developed worksheet were 87.50% with very good category. Based on the results, it can be concluded that student worksheet products based on direct instruction on quantities and measurements are very feasible to use.